Using pyrimidinecarboxylic acids as growth stimulants for Rhododendron ledebourii Pojark and Rhododendron smirnowii Trautv. - Tatiana V. VOSTRIKOVA; Andrey Yu. POTAPOV; Nadezhda V. STOLPOVSKAYA; Khidmet S. SHIKHALIEV (Acta Agriculturae Slovenica)
Synthesised organic compounds of pyrimidinecarboxylic acids are characterised by high biological activity, even when their concentrations are low. These compounds, when applied to the seeds of Rhododendron, a genus of woody plants, with concentrations of 0.01, 0.05, and 0.1 %, stimulate the growth of the plants. The effect is more obvious 3 months after the start of the experiment, rather than 7 months after. Thus, Rhododendron ledebourii Pojark. seedlings grew by 13.3-33.5 %, and Rhododendron smirnowii Trautv. seedlings grew by 29.6-48.1 %. Rhododendron ledebourii and Rhododendron smirnowii seedlings demonstrated similar direct correlations: when the concentration of 2-benzylamino-4-methyl-pyrimidine-5-carboxylic acid and 4-methyl-2-morpholin-4-pyrimidine-5-carboxylic acid (for Rhododendron ledebourii seeds only) rose from 0.01 to 0.1 %, the height of the seedlings increased. It is suggested using 4-methyl-2-piperidin-1-yl-pyrimidine-5-carboxylic acid, 2-benzylamino-4-methyl-pyrimidine-5-carboxylic acid, and 4-methyl-2-morpholin-4-pyrimidine-5-carboxylic acid at concentrations of 0.01, 0.05, and 0.1 % as growth stimulants for the species of Rhododendron genus.